The role of entrepreneurial intention in predicting vocational high school students’ employability - Fatwa Tentama; Sabrina Yusantri (Institute of Advanced Engineering and Science, 2020)
One of the factors that contribute to the level of employability is entrepreneurial intention. This study discusses the role of entrepreneurial intentions on students' employability. The population in this study was all students of grade XII of Vocational High School Koperasi Yogyakarta, Indonesia, consisting of 141 students. The sample in this study was 86 students. The sample selection was done by randomizing using a cluster random sampling technique. Methods of data collection used in this study are scales, employability scale, and entrepreneurial intentions scale. Analysis of the data used in this study is the product-moment analysis technique. The results of data analysis showed the correlation between entrepreneurial intentions and employability where r = 0.339 with p = 0.001 (p < 0.01), which showed a very significant positive correlation between the two variables at the research site. It means that the level of employability can be predicted based on entrepreneurial intention. The entrepreneurial intention contributed 11.5% to employability, and the remaining 88.5% can be influenced by other variables.